Four-way modeling of 4.2 K time-resolved excitation emission fluorescence data for the quantitation of polycyclic aromatic hydrocarbons in soil samples - Goicoechea, Hector Casimiro (2012)
A screening method for the soil analysis of 15 Environmental Protection Agency-polycyclic aromatic hydrocarbons (EPA-PAHs) is reported. The new method is based on the collection of 4.2 K fluorescence time-resolved excitation-emission cubes (TREECs) via laser-excited time-resolved Shpol'skii spectroscopy. 4.2 K fluorescence TREECs result from the superposition of fluorescence time-resolved excitation emission matrices recorded at different time windows from the laser excitation pulse. Potential interference from unknown sample concomitants is handled by processing the four-way 4.2 K fluorescence TREEC data arrays with either parallel factor analysis (PARAFAC) or unfolded partial least-squares/residual-trilinearization(U-PLS/RTL). The sensitivity of the two approaches makes possible to determine PAHs at the ng g-1 to pg g-1 concentration level with no need for sample pre-concentration. Its selectivity eliminates sample clean-up steps and chromatographic separation. These features reduce PAH loss, analysis time and cost. The method is environmentally friendly as the complete screening of the 15 EPA-PAHs takes only 250 μL of organic solvent per sample.